Quantitative risk assessment model of the presence of porcine epidemic diarrhea and African swine fever viruses in spray-dried porcine plasma - Sampedro, Fernando; Urriola, Pedro E.; van de Ligt, Jennifer L. G.; Schroeder, Declan C.; Shurson, Gerald C. (Frontiers in Veterinary Science, 2024)
There are no microbiological regulatory limits for viruses in animal feed and feed ingredients. A performance objective (PO) was proposed in this study to manufacture a spray-dried porcine plasma (SDPP) batch absent of any infectious viral particles. The PO levels of -7.0, -7.2 and -7.3 log TCID50/g in SDPP were estimated for three batch sizes (10, 15, and 20 tons). A baseline survey on the presence of porcine epidemic diarrhea virus (PEDV) in raw porcine plasma revealed a concentration of -1.0±0.6 log TCID50/mL as calculated using a TCID50-qPCR derived standard curve. The mean African swine fever virus (ASFV) concentration in raw plasma was estimated to be 0.6 log HAD50/mL (0.1-1.4, 95% CI) during a pre-clinical scenario (collected from asymptomatic and undetected viremic pigs). Different processing scenarios (baseline: spraydrying + extended storage) and baseline + ultraviolet (UV) radiation were evaluated to meet the PO levels proposed in this study. The baseline and baseline + UV processing scenarios were >95% and 100% effective in achieving the PO for PEDV by using different batch sizes. For the ASFV in SDPP during a pre-clinical scenario, the PO compliance was 100% for all processing scenarios evaluated. Further research is needed to determine the underlying mechanisms of virus inactivation in feed storage to further advance the implementation of feed safety risk management efforts globally.